The Pharmacological TAILS of Matrix Metalloproteinases and Their Inhibitors - Nabangshu Das; Colette Benko; Sean E. Gill; Antoine Dufour (MDPI AG, 2020)
Matrix metalloproteinases (MMPs) have been demonstrated to have both detrimental and protective functions in inflammatory diseases. Several MMP inhibitors, with the exception of Periostat®, have failed in Phase III clinical trials. As an alternative strategy, recent efforts have been focussed on the development of more selective inhibitors or targeting other domains than their active sites through specific small molecule inhibitors or monoclonal antibodies. Here, we present some examples that aim to better understand the mechanisms of conformational changes/allosteric control of MMPs functions. In addition to MMP inhibitors, we discuss unbiased global approaches, such as proteomics and N-terminomics, to identify new MMP substrates. We present some examples of new MMP substrates and their implications in regulating biological functions. By characterizing the roles and substrates of individual MMP, MMP inhibitors could be utilized more effectively in the optimal disease context or in diseases never tested before where MMP activity is elevated and contributing to disease progression.